Apport Des Images ETM+ Et Du Modèle Numérique De Terrain (MNT) A La Cartographie Des Fractures En Région Montagneuse : Secteur De Timia (Massif De l’Aïr, Nord Du Niger) - Alhassane, Illias; Sani, Abdou Babaye Maman; Issoufou, Sandao; Bachir, Saley Mahaman; Boureima, Ousmane (European Scientific Journal, ESJ, 2018)
Timia is located at the Aïr massifs region. This locality, which is the substratum that constituted the basement formations, has some difficulty of water supply. This present study focuses on fractures mapping to acquire the best knowledge of the fractured aquifer in Timia zone. The methodological approach is based on landsat7 image processing and DEM, especially directional filtering and shaded digital terrain models. These diverse processing has shown complementarity between the satellites images and DEM in linear mapping on the one hand and in establishing a lineaments map on the other hand. The lineament map showed that the fractures network is distributed in the following directions: N0°-N10°, N140°-N170°, N 70°- N100°, and N30°-N50°. These fractures map, which was allowed to increase the density of faults from the previous studies, were used to actualize hydrogeological knowledge and in determining the favorable sites for drilling boreholes in Timia locality.